2011
DOI: 10.3998/ark.5550190.0012.914
|View full text |Cite
|
Sign up to set email alerts
|

Bidentate Schiff bases derived from (S)-α-methylbenzylamine as chiral ligands in the electronically controlled asymmetric addition of diethylzinc to aldehydes

Abstract: A group of bidentate Schiff bases derived from enantiomerically pure (S)--methylbenzylamine was synthesized. Crystal structure was determined for three compounds. Schiff bases were used as chiral ligands in the asymmetric addition of Et2Zn to aldehydes. The obtained enantioselectivity was e.e.=8-94% depending on the substrate and the best was observed for (S,E)-2-(1-(1-phenylethylimino)-ethyl)phenol. The enantioselectivity increase was connected with the substituent-induced electronic effects in the substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Among them, the conformer s -1c is preferred over s -1a and s -1b by 2.25 and 1.41 kcal/mol, respectively. The computed conformer of lowest energy is in good agreement with the known single-crystal X-ray diffraction structure (Figure ) and Smith’s conformational analysis as well …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Among them, the conformer s -1c is preferred over s -1a and s -1b by 2.25 and 1.41 kcal/mol, respectively. The computed conformer of lowest energy is in good agreement with the known single-crystal X-ray diffraction structure (Figure ) and Smith’s conformational analysis as well …”
Section: Resultssupporting
confidence: 81%
“…Comparison of (left) the computed structure for the most stable conformer s -1c in vacuum obtained at the B3LYP/6-311++G** level of theory and (right) the reported single-crystal structure of s - 1 from ref .…”
Section: Resultsmentioning
confidence: 99%
“…However, recently, the extensive applicability of this transformation was reduced due to the unobtainability of appropriate catalysts for assigning a certain stereochemistry to the newly made stereogenic centers [22]. 2 BioMed Research International diethylzinc to aldehyde as shown in Scheme 6 [24]. They achieved an enantiomer excess (e.e) of 8 to 94% based on the substrate, and the finest was observed for (S, e)-2-(1-(1-phenylethylimino)-ethyl) phenol [24].…”
Section: Synthesis Of Chiral Schiffmentioning
confidence: 99%
“…2 BioMed Research International diethylzinc to aldehyde as shown in Scheme 6 [24]. They achieved an enantiomer excess (e.e) of 8 to 94% based on the substrate, and the finest was observed for (S, e)-2-(1-(1-phenylethylimino)-ethyl) phenol [24]. Additionally, chiral Schiff bases with substituent were reported to have strong influence on a catalyst's effectiveness, enantioselectivities, and reactiv-ities [14,25].…”
Section: Synthesis Of Chiral Schiffmentioning
confidence: 99%
See 1 more Smart Citation